The Analysis of Store Atmosphere and on Purchase Decision at Shelter Cafe Palembang - Siti Hilmina Mawaddati; Fetty Maretha (Department of Business Administration Politeknik Negeri Sriwijaya, 2022)
This study tried to analyze the effect of store ambience on the purchase decision of Shelter Cafe visitors in Palembang. By using purposive sampling, thirty visitors became the sample of respondents by filling out the questionnaires. Multiple linear regression analysis was then used to analyze the data. The result showed that store atmosphere had a positive and significant effect on the purchase decision.